2007
DOI: 10.1007/s11103-007-9234-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of expression profile of selected genes expressed during auxin-induced somatic embryogenesis in leaf base system of wheat (Triticum aestivum) and their possible interactions

Abstract: Somatic embryogenesis is a notable illustration of plant totipotency and involves reprogramming of development in somatic cells toward the embryogenic pathway. Auxins are key components as their exogenous application recuperates the embryogenic potential of the mitotically quiescent somatic cells. In order to unravel the molecular basis of somatic embryogenesis, cDNA library was made from the regeneration proficient wheat leaf base segments treated with auxin. In total, 1440 clones were sequenced and among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 96 publications
3
59
2
2
Order By: Relevance
“…Armstrong et al (2004) showed that 10% of the auxin-responsive genes were involved in metabolism of Arabidopsis in treated with 5 µM IAA for 1 h. Similar changes in genes related to cellular metabolism have been reported in plants treated with IAA (Goda et al 2004;Okushima et al 2005;Singla et al 2007). The IAA-induced changes in the levels of metabolites could be ascribed to altered changes in expression of appropriate genes induced by the auxin treatment.…”
Section: Gene Expression and Changes In Levels Of Metabolitessupporting
confidence: 60%
“…Armstrong et al (2004) showed that 10% of the auxin-responsive genes were involved in metabolism of Arabidopsis in treated with 5 µM IAA for 1 h. Similar changes in genes related to cellular metabolism have been reported in plants treated with IAA (Goda et al 2004;Okushima et al 2005;Singla et al 2007). The IAA-induced changes in the levels of metabolites could be ascribed to altered changes in expression of appropriate genes induced by the auxin treatment.…”
Section: Gene Expression and Changes In Levels Of Metabolitessupporting
confidence: 60%
“…In support of the expected similarities in SE-and ZE-related transcriptomes, an analysis of an embryogenic culture in rice revealed that out of 242 rice homologues of the genes that are essential for ZE in Arabidopsis, 87 % were expressed during SE (Su et al 2007). Further support for some type of convergence of the genetic determinants that control SE and ZE was provided by the observation that most of the genes that are differentially regulated during SE in various plants were revealed to represent the major TF families that are engaged in ZE (Singla et al 2007;Imin et al 2008;Chakrabarty et al 2010;Wisniewska et al 2012;Gliwicka et al 2013;Wickramasuriya and Dunwell 2015).…”
Section: Global Characteristics Of the Se-associated Tf Transcriptomesmentioning
confidence: 99%
“…Besides microarrays, EST sequencing in wheat (Singla et al 2007) and RNA-seq in Arabidopsis (Wickramasuriya and Dunwell 2015) and cotton (Yang et al 2012) have been applied in order to reveal SE-related transcriptomes. The microarray-based data showed that 1-12 % of all of the genes that were significantly modulated during embryogenic induction in different plants were found to encode TFs.…”
Section: Global Characteristics Of the Se-associated Tf Transcriptomesmentioning
confidence: 99%
“…In addition, the implementation of genomic expression methods in the recent decade has greatly speed up the identification of numerous genes with potential involvement in the determination of SE. With the use of transcriptome analysis, candidate SE-specific genes were identified in a number of plant species, including gymnosperms (Stasolla et al 2004;Aquea and Arce-Johnson 2008), Glycine max (ThibaudNissen et al 2003), Triticum aestivum (Singla et al 2007), cotton (Zeng et al 2006), maize (Che et al 2006), potato (Sharma et al 2008), oil palm (Low et al 2008) and Cyclamen persicum (Hoenemann et al 2010). The available data confirmed a substantial complexity of gene networks involved in the onset and progress of SE (Zeng et al 2007), in which genes with regulatory functions, such as transcription factors (TFs), are predominantly represented and predicted to have an essential role (Singla et al 2007).…”
Section: Introductionmentioning
confidence: 99%